A New Strategy in the Synthesis of Amide‐bearing Pyrrolizine from 2‐Pyroglutamic acid. Issue 11 (22nd March 2023) - Siddaraj, Ranjith; Ningegowda, Raghu; Swamy, Shivananju Nanjunda; Chandrashekharappa, Sandeep; Priya, Babu S
Abstract: The present synthetic methodology is related to the synthesis of novel azabicycloalkanes and their synthetic analogues. New and convenient synthetic routes were developed for access to the novel Pyrrolizine, and its analogue was synthesized using a multi‐step synthesis methodology. A novel efficient synthesis of the azabicyclic ring system via Michael addition followed by the intramolecular ring closing method of pyrrolizine has been developed utilizing deprotection of the CBz group by hydrogenation followed by in‐situ Michael addition and intramolecular cyclization reaction as the key step. This methodology can be further taken forward to the pharmaceutically active natural products containing azabicyclic ring systems. All the synthesized compounds were characterized by spectroscopic methods like I H‐NMR, 13 C‐NMR, LC‐MS, IR, and elemental analysis. Abstract : The present synthetic methodology is related to the synthesis of novel azabicycloalkanes and their synthetic analogues. New and convenient synthetic routes were developed for access to the novel Pyrrolizine, and its analogue was synthesized using a multi‐step synthesis methodology.